Menyibak Kebijaksanaan Amsal 2:1-22 dalam Semboyan Masyarakat Dayak: “Adil Ka'talino, Bacuramin Ka'saruga, Basengat Ka'jubata” - Jakarias; Wardoyo, Gregorius Tri; Firmanto, Antonius Denny (Perspektif, 2025)
This article focuses on Dayak slogans that are now emerging to the surface. This research explores the relationship between cultural traditions, scripture, and moral principles that develop among Dayak people. The novelty of this research is that it offers an intertextual way of reading, namely how Catholics read sacred texts by living them in their cultural context in social life which is so closely related to the ancestral tradition of living in harmony between tribes. This study uses a qualitative approach with a literature review method. The analysis was conducted to understand how local cultural values are integrated with religious teachings in the context of daily life. The findings of the study prove that the Dayak people are able to transform the tradition of violence and shamanism into a motto of unity (Adil ka' Talino), which reflects universal goodness and justice and abandons evil things that harm fellow humans. Thus, life must be harmonious and peaceful (Ba' curamin ka' Saruga). The value of Ba'sengat ka' Jubata reflects a higher spiritual consciousness, where people are completely dependent on the God they call (Jubata), because this life breathes from His power. This motto not only serves as a cultural identity but also as a tool to build social harmony in the midst of the diversity that exists in Kalimantan.